The Effect Of Multiple To Box Jump Training On Blocking Ability In Extracurricular Volleyball At SMP Negeri 11 Kota Bengkulu - Bimantara, Erwin Satria; Asnawati, Asnawati; Sumantri, Ajis (Utami Publisher, 2026)
This study aims to determine the Effect of Multiple to Box Jump Training on Blocking Ability in Extracurricular Volleyball Games at SMP Negeri 11 Bengkulu City. This type of research is a correlational study. The research sample was 20 people. The instruments used in this study were the leg muscle explosive power test and the blocking test in volleyball games. Based on the multiple to box jump and blocking ability of extracurricular volleyball games at SMP Negeri 11 Bengkulu City, rtable was obtained at 0.443 because the correlation coefficient between rxy = 0.92> 0.443 and a contribution of 92.85% which means that the contribution of multiple to box jump and blocking ability of extracurricular volleyball games at SMP Negeri 11 Bengkulu City is significant and large. Thus, the hypothesis that reads